2019
DOI: 10.15446/dyna.v86n209.75839
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pressure filtration coffee preparation methods (Coffea arabica L. var. Castillo) on antioxidant content and activity, and beverage acceptance

Abstract: The majority of pressure filtration methods for coffee preparation constitute acceptable alternatives for the obtention of coffee with bitter notes and body. In this study, antioxidant metabolite retention, antioxidant activity, and cup profiles were determined for coffee beverages prepared using five methods of pressure filtration. The methods which registered the highest antioxidant retention rates were Espresso, Moka, and Staresso. The highest hydroxycinnamic acid content was obtained with the Staresso, Esp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 47 publications
0
1
1
4
Order By: Relevance
“…Phenol content reported with Expresso and Mocca methods were 5,000 and 3,000 mg of gallic acid.100 g sample -1 , respectively (Ormaza-Zapata; Díaz-Arango; Rojano, 2019b), which presented values superior to those reported in the present study for the Ibrik and French Press methods. These presented higher levels of phenols in the beverage obtained.…”
Section: Values (N=3)contrasting
confidence: 77%
See 1 more Smart Citation
“…Phenol content reported with Expresso and Mocca methods were 5,000 and 3,000 mg of gallic acid.100 g sample -1 , respectively (Ormaza-Zapata; Díaz-Arango; Rojano, 2019b), which presented values superior to those reported in the present study for the Ibrik and French Press methods. These presented higher levels of phenols in the beverage obtained.…”
Section: Values (N=3)contrasting
confidence: 77%
“…On comparison of hydroxycinnamic acid content quantified with the direct contact methods (chlorogenic, caffeic, p-coumaric, and ferulic acids) to other preparation types described extensely in other studies, they were found to coincide in a range between 20 and 120 mg.100g of sample -1 , approximately (Ormaza-Zapata; Díaz-Arango; Rojano, 2019; Ormaza-Zapata; Díaz-Arango; Rojano, 2019b;Angeloni et al, 2019;Muñoz et al, 2020).…”
Section: Values (N=3)mentioning
confidence: 67%
“…También hay estudios del contenido de fenoles totales y flavonoides en bebidas de café preparadas de diversas formas. Se mostró que el preparado como "expreso" tuvo el mayor contenido de fenoles totales, 0,29 mmol EAG/g de café y de flavonoides 379 µmol ECq/g de café y se asoció a una mayor capacidad antioxidante 17 .…”
Section: Compuestos Bioactivos No Enzimáticosunclassified
“…Los métodos de extracción combinados para la preparación del café incluyen los de filtración a presión y son una alternativa aceptable para obtener un café con cuerpo y notas amargas (Ormaza Zapata et al, 2019). Además, los granos de café son fuentes ricas en compuestos polifenólicos con altas propiedades antioxidantes y actividad antiinflamatoria, entre estos compuestos se incluye a la cafeína y los ácidos clorogénicos (Bhattarai et al, 2022).…”
Section: Introductionunclassified
“…Algunas investigaciones han relacionado el contenido fenólico con el método de extracción. Ormaza- Zapata et al (2019) determinaron la retención de metabolitos antioxidantes, la actividad antioxidante y los perfiles de taza para bebidas de café preparadas utilizando cinco métodos de filtración a presión. En esta investigación se recomienda consumir el café utilizando los métodos Espresso o Moka (Ormaza Zapata et al, 2019).…”
Section: Introductionunclassified